PENGEMBANGAN SISTEM PENCATATAN DAN PELAPORAN INSIDEN KESELAMATAN PASIEN (IKP) BERBASIS WEB DI RUMAH SAKIT - Siti Zahro (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2021)
Background: In an effffort to improve patient safety in Hj. AnnaLasmanah Hospital Banjarnegara Regency, this studydeveloped a web-based incident reporting system. This is aneffffective tool with advantages suitable for promoting an openculture for patient safety.Objectives: Improve incident reporting mechanisms in hospitalconsidering the comfort, convenience and confifidentiality, sothat it can support the efffforts of improve patient safety.Methods:This was action research design, conducted at the Hj.Anna Lasmanah Hospital Banjarnegara Regency. Researchparticipants amounted to 7 (seven) people. The research beganwith the identifification of needs through interviews, observationand study of documentation. The process of making theprototype systems was based on the results of the identifificationof needs. The evaluation process was carried out using aquestionnaire, distributed to 40 participants to assess usability.While for evaluating importance, scientififically acceptable,transparency, and feasibility, we conducted observation andinterviews with participants. Interview data were analyzedqualitatively, through the process of data transcription, codingand categorization. Data from questionnaires done bycalculating the average.Results: This research resulted a prototype incident reportingsystem that accommodated to the basic needs of the user. Mostparticipants (91,96%) were satisfified with the applicationdeveloped. The prototype system is considered appropriate tobe applied in the hospital, with some suggestions for the needfor improvement regarding the application program, networkinfrastructure and human resource capacity.Conclusion: A prototype system developed was consideredcan improve incident reporting mechanisms in hospitalconsidering the comfort, convenience and confifidentiality, sothat it can support the efffforts of improve patient safety.